Vegetal Oil Transesterification Using Tetranuclear Zinc-Diterpene Clusters as the Catalysts - Martínez-Torres, Mayra A.; Talavera-Alemán, Armando; Zamudio-Jaime, Karina; Villagómez-Guzmán, Ana K.; Quevedo-Tinoco, Lirenny; Rico, José L.; Rosas, Gerardo; del Río, Rosa E.; Gómez-Hurtado, Mario A.; Rodríguez-García, Gabriela (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Organic natural products, particularly vegetal secondary metabolites, represent a highlighted source for molecules usable for many purposes, including synthesizing catalysts. Biocompatible metals can yield interesting coordination complexes to provide sustainable and valuable compounds. In the present paper, the unique in their class (μ4-oxo)-hexakis(μ2-beyerenate)-tetra-zinc(II) (1) and (μ4-oxo)-hexakis(μ2-kaurenate)-tetra-zinc(II) (2) are suggested as eco-friendly catalysts for transesterification reactions. The heterogeneous/homogeneous catalytic potential of 1 and 2 was revealed using olive oil as an equilibrated saturated-unsaturated fatty acid mixture and methanol as the nucleophile and solvent. Systematic variations in reaction conditions were achieved herein, including temperature, catalyst mass, methanol volume, and reaction time, allowing a yield of up to 97% in the transesterification process. The FAME product was characterized using 1H NMR and GC-MS, and the calorific value of 33.72 MJ/kg was concordant with the literature. The thermogravimetric, powder X-ray diffraction, and Scanning Electron Microscopy experiments complemented the catalyst properties before and after the catalytic tests. This finding suggests that coordination complexes using natural products as ligands represent a new class of potential ecological catalysts from industry and scientific research in crucial chemical reactions. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).